2012
DOI: 10.1007/s10646-012-0992-2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of environmentally relevant lead and zinc in halophyte Suaeda salsa by NMR-based metabolomics

Abstract: a b s t r a c tMercury is a highly risky heavy metal contaminant in intertidal zones in the Yellow River Delta (YRD). Suaeda salsa is a native halophyte in the YRD. In this work, we investigated the toxicological effects of mercury (20 mg L À 1 ) in S. salsa under environmentally relevant salinity (500 mM). The metabolic responses included the increased amino acids and decreased succinate, fructose, glucose, fumarate and ferulate in above-ground part of S. salsa exposed to mercury. The expression levels of INP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…showed the biological response of halophytic plant suaeda salsa under Pb, Zn, and Hg exposure using NMR‐based metabolomics combined with antioxidant enzyme activities measurement []. On the one hand, the short (1 week) and long term (1 month) toxicological effects of environmentally relevant concentrations of Pb and Zn were characterized in S. salsa . In this study, after metal exposure for 1 week, no significant metabolic responses were detected in root tissues, which involve the increase of isocaproate, glucose, and fructose, and decrease of malate, citrate, and sucrose in root tissues of S. salsa exposed to Pb for 1 month.…”
Section: Environmental Metabolomics Exposure Experimentsmentioning
confidence: 75%
See 2 more Smart Citations
“…showed the biological response of halophytic plant suaeda salsa under Pb, Zn, and Hg exposure using NMR‐based metabolomics combined with antioxidant enzyme activities measurement []. On the one hand, the short (1 week) and long term (1 month) toxicological effects of environmentally relevant concentrations of Pb and Zn were characterized in S. salsa . In this study, after metal exposure for 1 week, no significant metabolic responses were detected in root tissues, which involve the increase of isocaproate, glucose, and fructose, and decrease of malate, citrate, and sucrose in root tissues of S. salsa exposed to Pb for 1 month.…”
Section: Environmental Metabolomics Exposure Experimentsmentioning
confidence: 75%
“…Other experiments carried out by Wu et al . showed the biological response of halophytic plant suaeda salsa under Pb, Zn, and Hg exposure using NMR‐based metabolomics combined with antioxidant enzyme activities measurement []. On the one hand, the short (1 week) and long term (1 month) toxicological effects of environmentally relevant concentrations of Pb and Zn were characterized in S. salsa .…”
Section: Environmental Metabolomics Exposure Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bioindicators, mostly enzymes and metabolites in seawater organisms, have been developed and tested to evaluate the contamination and toxicity of Pb 2+ as a pollutant [36][37][38][39]. The tested biochemical enzymes were catalase, reduced glutathione, glutathione S-transferase, lipid peroxides, superoxide dismutase and alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Pb is not essential in plant organisms and can prove toxic. Wu et al (2012) found that Pb could induce osmotic and oxidative stresses and disturbances in energy metabolism in S. salsa after exposure for 1 month. According to Ross (1994), Pb concentrations were considered to have toxic effect on plants as the values exceeded the phytotoxic range (30~300 mg/kg).…”
Section: Variations Of Heavy Metals In Plants and Sedimentsmentioning
confidence: 96%